Accident risk identification and its impact analyses for strategic construction safety management - Chi, Seokho; Han, Sangwon; Kim, Dae Young; Shin, Yoonjung (Journal of Civil Engineering and Management, 2015)
The study presented in this paper reviewed 9,358 accidents which occurred in the U.S. construction industry between 2002 and 2011, in order to understand the relationships between the risk factors and injury severity (e.g. fatalities, hospitalized injuries, or non-hospitalized injuries) and to develop a strategic prevention plan to reduce the likelihood of fatalities where an accident is unavoidable. The study specifically aims to: (1) verify the relationships among risk factors, accident types, and injury severity; (2) determine significant risk factors associated with each accident type that are highly correlated to injury severity; and (3) analyse the impact of the identified key factors on accident and fatality occurrence. The analysis results explained that safety managers’ roles are critical to reducing human-related risks – particularly misjudgement of hazardous situations – through safety training and education, appropriate use of safety devices and proper safety inspection. However, for environment-related factors, the dominant risk factors were different depending on the different accident types. The outcomes of this study will assist safety managers to understand the nature of construction accidents and plan for strategic risk mitigation by prioritizing high frequency risk factors to effectively control accident occurrence and manage the likelihood of fatal injuries on construction sites.